Organic dairy farming: impacts on insect-flower interaction networks and pollination - Stout, Jane (My University, 2011)
1. Pollination interactions comprise a network of connections between ?owers and insect visitors. They are crucial for reproductive success in many angiosperms but are threatened by intensive agricultural practices. Although less intensive approaches, including organic farming, could improve farmland biodiversity, it is not clear whether or not these approaches enhance wild plant pollination and the stability of insect??ower interaction networks. 2. We investigated the e?ects of organic vs. conventional farming on insect??ower interaction network size and structure, bee and hover?y diversity, and pollination in 10 pairs of organic and conventional dairy farms in the Republic of Ireland. 3. We found that insect??ower interaction networks on organic farms were larger and more asymmetrically structured than networks on conventional farms. Overall, however, networks contained fewer taxa and niche overlap and plant ? animal ratios were relatively low compared with previously documented insect??ower interaction networks. Organic farms did attract higher numbers of bees partly because of higher ?oral abundances (mainly Trifolium sp.). Hover?y evenness was greater in organic farms but neither abundance, richness nor evenness was related to ?oral abundance, suggesting organic farms provide additional resources for hover?ies. Pollination of Crataegus monogyna hawthorn was higher on organic farms, although pollen deposition was limited. 4. Synthesis and applications. Organic dairy farming can increase the size and alter the structure of insect??ower interaction networks. However, network stability was not improved and all networks (organic and conventional) were vulnerable because of their small size, low niche overlap and low plant ? animal ratios. Nonetheless, organic farming provided more ?owers that attracted more ?ower visitors and improved pollination of C. monogyna. We suggest that strategic management of important ?owers for pollinators in hedgerows and pastures should be endorsed in agri-environmental schemes. Sowing Trifolium spp., and allowing these plants to ?ower, could bene?t bees, but more research into hover?y ecology is necessary before realistic conservation recommendations can be made for this group. We conclude that organic farming, although not the solution in its present form, can bene?t insect biodiversity, insect??ower interaction networks and insect-mediated pollination.
PUBLISHED
Keywords: Botany; Pollination interactions; Smart & Sustainable Planet; Biodiversity and Conservation; Ecology